Effectiveness of breastfeeding interventions delivered to fathers in low‐ and middle‐income countries: A systematic review. Issue 4 (8th May 2018) - Tadesse, Kidane; Zelenko, Oksana; Mulugeta, Afework; Gallegos, Danielle
Abstract: Adequate support for lactating mothers is crucial to improve the rates of early initiation, exclusive, and continued breastfeeding. Maternal breastfeeding intention and ongoing breastfeeding duration are strongly predicted by their partners' breastfeeding beliefs. Partner support has a significant effect on improving rates of any and exclusive breastfeeding, when compared with professional support, particularly in low‐income populations. This systematic review investigates the effectiveness of breastfeeding interventions targeting fathers in low‐ and middle‐income countries (LMIC). A systematic literature search was undertaken on Medline (EBSCOhost), PsycInfo, CINAHL, and Scopus databases and via manual searching. Inclusion criteria were experimental or quasiexperimental designs targeting fathers from LMIC, which measured either breastfeeding initiation, breastfeeding exclusivity, or duration of breastfeeding as the main outcomes. No time restriction was put in place, and all articles were published in English. The quality of selected papers was assessed using the Joanna Briggs Institute tool. A total of 8 articles were included from 6 interventions: 2 quasiexperimental and 4 randomized control trials. All interventions involved breastfeeding education targeting fathers; 2 were given only to fathers, and 4 delivered to both fathers and mothers. Among these interventions, 2 measured both early initiation and exclusive breastfeeding; one exclusive breastfeeding only; one exclusive breastfeeding, knowledge, and attitudes; one exclusive breastfeeding and knowledge; and one breastfeeding, continued breastfeeding, and awareness. Across all interventions, breastfeeding education showed significant improvement in breastfeeding outcomes in the intervention compared with the control groups. In summary, breastfeeding education interventions targeting fathers in LMIC are effective in improving early initiation of breastfeeding, exclusive breastfeeding, and continued breastfeeding. Thus, breastfeeding promotion should consider the education and involvement of fathers in the intervention.